Effect of rapid thermal annealing on InAs/GaAs quantum dot solar cells. Issue 2 (1st April 2015) - Lam, Phu Minh; Wu, Jiang; Hatch, Sabina; Kim, Dongyoung; Tang, Mingchu; Liu, Huiyun; Wilson, James; Allison, Rebecca
Abstract : The effect of post‐growth annealing on InAs/GaAs quantum dot solar cells (QDSCs) is studied. A significant improvement in photoemission, photocurrent density and spectral response was observed with post‐growth annealing. The optimal anneal temperature was found to be 700°C, which lead to an 18% improvement in current density from 4.9 mA cm −2 for as‐grown sample to 5.8 mA cm −2 . We assign this enhanced performance to the reduced density of inherent point defects that was formed at the quantum dot (QD) and GaAs barrier. Post‐growth thermal annealing of QDSCs is demonstrated as a simple route for achieving improved device performance.